Pengaruh Kinerja Keberlanjutan Terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Yusril Ihzamaihendra; Ansyarif Khalid; Ismail Badollahi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of sustainability performance on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research is a type of quantitative research. The data used are primary data obtained from 6 manufacturing companies listed on the Indonesia Stock Exchange in 2020-2023 with a total of 24 observation data during 4 years of observation. The data collection technique used is documentation. Data were analyzed using multiple linear regression analysis with SPSSV.27 software. The results of the study show that economic performance (X1) has a positive and significant effect on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) This is evidenced by the t-calculated value of 4.055 > t table 1.725 and a significance value of 0.001 < 0.05. Meanwhile, social performance (X2) has been proven to have a negative and significant effect on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This is evidenced by the t-calculated value of -4.495 > t table 1.725 and a significance value of 0.001 < 0.05 and the environmental performance variable (X3) also has a positive and significant influence on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This is evidenced by the t-calculated value of 3.074 > t-table 1.725 and a significant value of 0.006 < 0.05. Partially, these three variables have a significant influence on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a value of (R2) of 0.682.